Non-linear mechanical, electrical and thermal phenomena in piezoelectric crystals - Warkusz, F.; Linek, A. (Condensed Matter Physics, 2003)
Mechanical, electrical and thermal phenomena occurring in piezoelectric crystals were examined by non-linear approximation. For this purpose, use was made of the thermodynamic function of state, which describes an anisotropic body. Considered was the Gibbs function. The calculations included strain tensor εij = f(σkl , En, T), induction vector Dm = f(σkl , En, T) and entropy S = f(σkl , En, T) as function of stress σkl , field strength En and temperature difference T. The equations obtained apply to anisotropic piezoelectric bodies provided that the “forces” σkl , En, T acting on the crystal are known.